Frank and Ernest - Day, Alexandra (New York : Scholastic Inc., 1988)
An elephant and a bear take over a diner and find out about responsibility and food language.
School Library Journal starred
Booklist
Bulletin (Center for Childrens's books)
3.8
K-3
Keywords: Elephants -- Fiction; Bears -- Fiction; Diners (Restaurants) -- Fiction; Responsibility -- Fiction; Elephants -- Fiction; Bears -- Fiction; Responsibility -- Fiction; Restaurants, bars, etc. -- Fiction